Early decreased TLR2 expression on monocytes is associated with their reduced phagocytic activity and impaired maturation in a porcine polytrauma model - Schimunek, Lukas; Serve, Rafael; Teuben, Michel P. J.; Stoermann, Philipp; Auner, Birgit; Woschek, Mathias; Pfeifer, Roman; Horst, Klemens; Simon, Tim-P.; Kalbitz, Miriam; Sturm, Ramona; Pape, Hans-C.; et al. (PLoS ONE, 2017)
In their post-traumatic course, trauma patients suffering from multiple injuries have a high risk for immune dysregulation, which may contribute to post-injury complications and late mortality. Monocytes as specific effector cells of the innate immunity play a crucial role in inflammation. Using their Pattern Recognition Receptors (PRRs), notably Toll-Like Receptors (TLR), the monocytes recognize pathogens and/or pathogen-associated molecular patterns (PAMPs) and organize their clearance. TLR2 is the major receptor for particles of gram-positive bacteria, and initiates their phagocytosis. Here, we investigated the phagocytizing capability of monocytes in a long-term porcine severe trauma model (polytrauma, PT) with regard to their TLR2 expression. Polytrauma consisted of femur fracture, unilateral lung contusion, liver laceration, hemorrhagic shock with subsequent resuscitation and surgical fracture fixation. After induction of PT, peripheral blood was withdrawn before (-1 h) and directly after trauma (0 h), as well as 3.5 h, 5.5 h, 24 h and 72 h later. CD14+ monocytes were identified and the expression levels of H(S)LA-DR and TLR2 were investigated by flow cytometry. Additionally, the phagocytizing activity of monocytes by applying S. aureus particles labelled with pHrodo fluorescent reagent was also assessed by flow cytometry. Furthermore, blood samples from 10 healthy pigs were exposed to a TLR2-neutralizing antibody and subsequently to S. aureus particles. Using flow cytometry, phagocytizing activity was determined. P below 0.05 was considered significant. The number of CD14+ monocytes of all circulating leukocytes remained constant during the observational time period, while the percentage of CD14+H(S)LA-DR+ monocytes significantly decreased directly, 3.5 h and 5.5 h after trauma. The percentage of TLR2+ expressing cells out of all monocytes significantly decreased directly, 3.5 h and 5.5 h after trauma. The percentage of phagocytizing monocytes decreased immediately and remained lower during the first 3.5 h after trauma, but increased after 24 h. Antagonizing TLR2 significantly decreased the phagocytizing activity of monocytes. Both, decreased percentage of activated as well as TLR2 expressing monocytes persisted as long as the reduced phagocytosis was observed. Moreover, neutralizing TLR2 led to a reduced capability of phagocytosis as well. Therefore, we assume that reduced TLR2 expression may be responsible for the decreased phagocytizing capacity of circulating monocytes in the early post-traumatic phase.
CRIS-Team Scopus Importer:2020-12-21